Vascular Complications in Individuals with Type 2 Diabetes Mellitus Additionally Increase the Risk of Femoral Neck Fractures Due to Deteriorated Trabecular Microarchitecture - Cirovic, Aleksandar (Calcif Tissue Int, 2021)
Individuals with diabetes mellitus type 2 (T2DM) have an increased risk of hip fracture, especially if vascular complications are present. However, microstructural origins of increased bone fragility in T2DM are still controversial. DXA measurement of the contralateral hip and three-dimensional microCT analyses of femoral neck trabecular microarchitecture were performed in 32 individuals (26 women and 6 men, 78 ± 7 years). The specimens were divided to two groups: T2DM individuals with hip fracture (DMFx, n = 18) and healthy controls (CTL, n = 14). DMFx group consisted of individuals with vascular complications (DMFx_VD, n = 8) and those without vascular complications (DMFx_NVD, n = 10). T-score was significantly lower in DMFx_VD and DMFx_NVD than in controls (p < 0.001). BV/TV, Tb.N, Tb.Sp, SMI, and FD varied among DMFx_NVD, DMFx_VD, and CTL groups (p = 0.023, p = 0.004, p = 0.008, p = 0.001, p = 0.007, respectively). Specifically, BV/TV of DMFx_VD was significantly lower than that of DMFx_NVD group (p = 0.020); DMFx_NVD group had higher Tb.N and lower Tb.Sp compared with DMFx_VD (p = 0.006, p = 0.012, respectively) and CTL (p = 0.026, p = 0.035, respectively). DMFx group and healthy controls showed similar BV/TV, Tb.Th, Tb.N, Tb.Sp, Conn.D, DA, and FD (p = 0.771, p = 0.503, p = 0.285, p = 0.266, p = 0.208, p = 0.235, p = 0.688, respectively), while SMI was significantly higher in controls (p = 0.005). Two distinct phenotypes of bone fragility were identified in T2DM patients: patients with vascular complications showed impaired trabecular microarchitecture, whereas bone fragility in the group without vascular complications was independent on trabecular microarchitecture pattern. Such heterogeneity among T2DM patients may explain contradicting literature data and may set a basis for further studies to evaluate fracture risk related to T2DM. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s00223-021-00894-5.